2020
DOI: 10.31234/osf.io/8qm7s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of Household Structure and Presence of Children in the Household with Mental Distress during the COVID-19 Pandemic

Abstract: Purpose: The objectives of the current study were to: (1) assess the impact of household structure (i.e. living alone compared to living with children, a partner, or both) and presence of children on mental distress during the COVID-19 pandemic; and (2) determine whether these associations are moderated by income or sex.Results: A total of 2,524 adults aged 25-55 were included in the analytic sample. Multivariable linear regression models were used to examine associations between explanatory variables and men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, there is evidence to suggest that mental health trends are not uniform, and that families' mental health during COVID-19 may differ based on several factors. For example, some research on the impact of COVID-19 on young children and their caregivers suggests that adverse mental health effects do not extend to young children (Gassman-Pines et al, 2020;Saleem et al, 2022) and their caregivers (Smail et al, 2020). Similarly, some research documenting the impact of COVID-19 on minoritized families suggests that despite a clear disproportionate impact in terms of COVID-19 exposure (Raviv et al, 2021), discrimination experiences during COVID-19 (Ruiz et al, 2020) and greater increases in unemployment related to the pandemic (Gezici & Ozay, 2020), minoritized children show unique mental health trends including no changes and even improvements in mental health symptoms during the pandemic as compared to prior (Bhogal et al, 2021;Penner et al, 2021;Raviv et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is evidence to suggest that mental health trends are not uniform, and that families' mental health during COVID-19 may differ based on several factors. For example, some research on the impact of COVID-19 on young children and their caregivers suggests that adverse mental health effects do not extend to young children (Gassman-Pines et al, 2020;Saleem et al, 2022) and their caregivers (Smail et al, 2020). Similarly, some research documenting the impact of COVID-19 on minoritized families suggests that despite a clear disproportionate impact in terms of COVID-19 exposure (Raviv et al, 2021), discrimination experiences during COVID-19 (Ruiz et al, 2020) and greater increases in unemployment related to the pandemic (Gezici & Ozay, 2020), minoritized children show unique mental health trends including no changes and even improvements in mental health symptoms during the pandemic as compared to prior (Bhogal et al, 2021;Penner et al, 2021;Raviv et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these studies did not specifically examine the experiences of caregiving for young children. Practices associated with caring for young children, such as consistent routines, may promote caregiver well-being (Gassman-Pines et al, 2020;Prime et al, 2020;Smail et al, 2020). One study found a larger increase in depression and anxiety for caregivers who were balancing home schooling and work responsibilities simultaneously and had difficulty obtaining child care, as compared to those who were not facing these same challenges (Racine et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, parents who struggled with work-family balance as a result of the pandemic reported higher levels of stress and greater marital conflict (Chung et al, 2020). Although a study by Smail et al (2020) provided evidence that having young children was associated with decreases in mental distress during the pandemic, the weight of evidence suggests that many families struggled to manage the demands of job-related changes when they had children to attend to as well.…”
Section: Covid-19 As a Relational Transitionmentioning
confidence: 99%